Treatment-assessment of Zygoma-tripod, -quadripod, -arch and Orbital floor Fractures in the Elderly Patient: Results of a Longitudinal Clinical Study of 20 years (1995-2015) with 1318 Patients in a General Traumatology-department and Evidence-based Treatm - Angelo Troedhan (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
The ever growing population of elderly patients aged 70 years and onwards are prone to facial injuries caused by a general degrading medical and mental state. Main cause for zygoma-tripod, -quadripod, -arch and orbital floor fractures are falls, followed by traffic accidents and only to a small extent violence. Surgical reduction for these types of fractures is recommended but not correlated to the general medical and mental state of this patient-group. Aim of the study was to compare the outcomes of surgical treatment versus non-surgical observation. Between 1995 and 2014 a total of 1318 patients - hospitalized for isolated zygoma- and correlated fractures - were initially screened for cause of accident, pain, hyp/anaesthesia of the corresponding infraorbital nerve, mandible mobility, facial emphysema/haematoma and diplopia and then distributed into three different groups: no functional and/or cosmetic surgery indication (X), surgery indication but denied by internist and/or anaesthesist due to high general medical risks (Y) and surgery indication and released for surgery by internist/anaesthesist (Z). Follow up for each group was performed on day 5, 7 and 1 month after date of injury. Pain assessment revealed a significant higher pain-load for group Z on the 5th and 7th day after injury. Mandible mobility, facial emphysema/haematoma and diplopia improved significantly better in group X and Y on day 5, 7 and after 1 month compared to group Z. Hyp/anaesthesia of the corresponding infraorbital nerve improved generally but not significant between all three groups. The results of this study suggest that indication for closed or even more for open-reduction surgery of isolated midface-bone fractures should be applied very restrictive and only in accordance with specialists for internal medicine and anaesthesiology for elderly patients and non-surgical observation might lead to better results both for life-quality and remaining life-time from the patients point of view.